Persepsi Pasien terhadap Kualitas Pelayanan Rawat Jalan Pada Puskesmas Di Kabupaten Buleleng - Rasnidiati, Komang Ayu Pitri; Subawa, Nyoman Sri (Jurnal ilmiah Manajemen Publik dan Kebijakan Sosial, 2020)
This study aims to determine the patient's perceptions of the outpatient services quality at Sawan I Public Health Center of Buleleng District. The research type used in this study is survey research with quantitative descriptive methods and to find out patient perceptions of the outpatient services quality refers to KEPMENPAN number 25/2004 concerning on General Guidelines for Community Satisfaction Index Preparation. Population in this study were outpatients as many as 150 respondents. The sample technique used in this study was the average value per service element to obtain the results of 150 respondents. The results of this study indicate that: (1) The implementation of outpatient services in Sawan I Public Health Center based on patient perceptions is categorized as very good with the value of the Community Satisfaction Index of 82.11 percent; (2) The patient's perception of the reliability of outpatient services is perceived in the good category with a value of 73.56 percent; (3) Patient perceptions of responsiveness of outpatient services are perceived to be in the excellent category of 57.33 percent; (4) The patient's perception of the guarantee of outpatient services is perceived in the good category of 58.84 percent; (5) The patient's perception of the attention of outpatient services is perceived in the good category of 71.78 percent; (6) The patient's perception of direct evidence of outpatient services is perceived in the good category of 72 percent.s